2020
DOI: 10.1111/trf.15717
|View full text |Cite
|
Sign up to set email alerts
|

The donors perceived positive and negative effects of blood donation

Abstract: BACKGROUND Occasionally blood donation has a negative influence on some donors, while others express feelings of increased energy or wellbeing after donation. Some donors even report symptoms such as headache or feelings of unease indicating “it is time to donate blood again.” This study aims to determine symptoms and frequencies of blood donors experiencing positive and negative effects of blood donation, and study possible associations with sex, age, body mass index, smoking status, and hemoglobin level. STU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
24
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(33 citation statements)
references
References 18 publications
5
24
4
Order By: Relevance
“…Other characteristics, such as smoking status or ethnicity may also affect symptoms after whole blood donation. 6,12 Fatigue was the most commonly reported postdonation symptom in both male and female donors, which generally is in line with previous studies. We found a low percentage of donors reporting severe problems for one or more post-donation symptoms compared to previous studies.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Other characteristics, such as smoking status or ethnicity may also affect symptoms after whole blood donation. 6,12 Fatigue was the most commonly reported postdonation symptom in both male and female donors, which generally is in line with previous studies. We found a low percentage of donors reporting severe problems for one or more post-donation symptoms compared to previous studies.…”
Section: Discussionsupporting
confidence: 90%
“…7,26 This finding may be explained by a selection process of donors experiencing post-donation symptoms to stop donating. 6 Male donors with higher blood pressure reported higher energy levels and better quality of sleep after donating whole blood compared to male donors with low blood pressure. Previous research has reported that blood donation may temporarily decrease blood pressure, resulting in a decrease in complaints such as headache.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations